Using the J-Mix as an interactive tool to teach writing to year 4 Pupils of SK Goebilt, Kuching / Ardi Pawi - Pawi, Ardi (2007)
This research aimed to find out the effectiveness of using a computer teaching tool - the J-Mix to teach writing to a group of Year 4 pupils who were weak in writing. The J-Mix would help these low proficiency pupils in improving their writing skill. Treatment in the form of J-Mix activities focusing on arranging jumble-up words to form meaningful sentences were used to help the pupils. The findings revealed that by using the J-Mix, and as shown in the 5 tests, the low ability pupils were able to improve their writing. It also aided in increasing the pupils’ level of interest towards the learning the language and helped promoting active participation from the pupils.